Population Pharmacokinetics of Semaglutide for Type 2 Diabetes - Overgaard, Rune V. (Diabetes Ther, 2019)
INTRODUCTION: The aim of the present analysis was to characterise the absorption, distribution and elimination of semaglutide by means of population pharmacokinetic (PK) models using data from nine clinical pharmacology trials conducted in both healthy subjects and those with type 2 diabetes. METHODS: Data were obtained from trials with subcutaneous and intravenous administration of semaglutide that utilised frequent PK sampling and included a total of 353 subjects with 10,573 concentration values. RESULTS: Semaglutide PK properties across trials, drug product strengths and populations were well characterised by a two-compartment model with first-order absorption and elimination. For a typical subject with type 2 diabetes, clearance was estimated to be 0.0348 L/h [95% confidence interval (CI) 0.0327–0.0369 L/h], and the central and peripheral volumes were estimated to be 3.59 L (95% CI 3.28–3.90 L) and 4.10 L (95% CI 3.78–4.42 L), respectively (i.e. a total volume of distribution of 7.7 L). Interindividual variation was low (~ 15%) for both clearance and volumes of distribution, with low residual error (< 5%). Clearance and the total volume of distribution were approximately proportional to body weight. Minor differences were identified between healthy subjects and subjects with type 2 diabetes with respect to clearance and absorption rate, and between injection sites with respect to bioavailability. CONCLUSIONS: A novel two-compartment model was developed to provide the general characteristics of semaglutide absorption following subcutaneous administration, and of distribution and elimination across administration routes. Semaglutide PK was shown to be predictable across populations and administration routes and within subjects, and was primarily influenced by body weight. FUNDING: Novo Nordisk, Bagsværd, Denmark. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1007/s13300-019-0581-y) contains supplementary material, which is available to authorized users.